PENGUATAN KAPASITAS ASESOR BAN-PDM MELALUI PELATIHAN LURING DALAM IMPELEMENTASI INSTRUMEN AKREDITASI TERBARU - Hasanah, Nur; Wakano, Abidin; Hamizar, Arizal; Marantika, Juliaans E.; Limba, natasija; Malasari, Dewi Qhuril; Matitaputty, Jenny Koce; Tamaela, Eduard Yohannis (MAJU : Indonesian Journal of Community Empowerment, 2024)
The 2024 BAN-PDM Assessor Training was held to strengthen the capacity of assessors in implementing the latest Accreditation Instrument for Primary and Secondary Education Units. This training focused on enhancing assessors' understanding and skills in the accreditation process, including data collection techniques and the use of the accreditation information system, SISPENA. The training method involved a combination of theoretical and practical approaches, including lectures, accreditation process simulations, and hands-on practice with SISPENA. The activities began with theoretical introduction, followed by data collection simulations, document analysis, and SISPENA usage practice. The training was conducted in person over three days, divided into several sessions focusing on direct interaction, group discussions, and practical exercises. The results showed a significant improvement in assessors' understanding and skills in using the accreditation instrument and SISPENA. Participants successfully applied data collection techniques and operated the system effectively, gaining practical skills to conduct field accreditation. The training successfully prepared assessors to face accreditation challenges in Maluku Province more efficiently and effectively.